MENINGKATKAN KREATIVITAS DESAIN FLYER DIGITAL MENGGUNAKAN APLIKASI CANVA MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) - Juwairia Juwairia; Dewi Koryati; Dian Eka Amrina; Usmi Sintara (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
This study aims to develop project-based classroom learning with the Project Based Learning ((PjBL) learning model to increase students' creativity in making digital flyer designs using the Canva application. This research method uses Classroom Action Research (CAR). The population of this study was all students of class XI BDP at SMK Negeri 1 Pemulutan. The sample in this study was selected by purposive sampling. Data collection techniques used Focus Group Discussion (FGD), interview methods, and observations. The data analysis technique used was descriptive qualitative data analysis. researcher An shows that the Project based Learning learning model has an influence in increasing students' creativity in designing digital flyers using the Canva application. Making this digital flyer is one of the concrete evidences that students can create promotional media creatively according to the demands of the business world/industrial world, train students' creativity, and improve students' skills in designing flyers into a business opportunity.